Rating agencies: Foreseeing the new forms of measuring political and credit risks - Teixeira, Maria Emília (2018)
The security, credibility and growth of a country, corporation or product are many times measured by ratings given for certain entities, for instance, the risk notations periodically published by major rating agencies. As a matter of fact, the investor's guide their investment strategy by such classifications. The present research enable us to develop a careful "free" review of the 2007/2008 financial crisis causes, consequently we can state that their ratings had some correction problems that would be manipulated by "hidden" interest and "actors". It's required to find out new measurement techniques of the corporate and countries investment risk. To develop our research, we chose to analyze the political and credit risk. Considering the extremely volatile political risk, it would occur in an unexpected concern, as well as, would be supported in a revolution or in riots, and, it would be a change through a Government change and/or laws changes implemented.